Clusters, Chains and Compliance: Corporate Social Responsibility and Governance in Football Manufacturing in South Asia - Lund-Thomsen, Peter (Journal of business ethics, 2010)
A recent concern in the debate on corporate social responsibility (CSR) in developing countries relates to the tension between demands for CSR compliance found in many global value chains (GVCs) and the search for locally appropriate responses to these pressures. In this context, an emerging and relatively understudied area of interest relates to small firm industrial clusters. Local clusters offer the potential for local joint action, and thus a basis for improving local compliance on CSR through collective monitoring and local governance. This article explores the interrelationship between global governance, exercised through GVC ties, and local governance, via cluster institutions, in ensuring compliance with CSR pressures. It undertakes a comparative analysis of two leading export-oriented football manufacturing clusters in South Asia that have both faced common challenges on child labour. The article shows that both forms vertical and horizontal governance have played a part in shaping the response of the two clusters on child labour. Moreover, these two distinct forms of governance have also led to quite differentiated outcomes in terms of forms of work organization and child labour monitoring. This raises broader questions on how global CSR demands can locally be better embedded and the conditions under which football stitchers labour in these new work forms.